1975
DOI: 10.1002/bit.260170611
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of biosynthesis of polyene macrolide antibiotics in batch cultures: Cell maturation time

Abstract: SummaryThe changes in several parameters of the candicidin fermentation (total, mycelium-associated, and extracellular product formation ; growth rate; DNA content; glucose utilization; dissolved oxygen in the broth; and oxygen uptake rate) during the trophophase-idiophase transition are compared with previously reported data for the polyene macrolides, candidin and candihexin. The maturation time, t,, and the product formation rate constant, k,, have been calculated for each of the three polyene macrolides us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…Similar observations were made for penicillin production at 0.007m 3 , where the speci®c penicillin production rate was aected below 30% air saturation, whereas the OUR was aected below 7% (Vardar and Lilly, 1982). The C crit for antibiotic production from S. lavendulae and S. griseus were also found to be 20% air saturation, respectively (Kojima, l995;Martin and McDaniel, 1975). The dierence between C crit for growth and production shows that additional dissolved oxygen requirements were needed for pneumocandin production.…”
Section: Separation Of the Impact Of Agitation And Dissolved Oxygensupporting
confidence: 64%
See 1 more Smart Citation
“…Similar observations were made for penicillin production at 0.007m 3 , where the speci®c penicillin production rate was aected below 30% air saturation, whereas the OUR was aected below 7% (Vardar and Lilly, 1982). The C crit for antibiotic production from S. lavendulae and S. griseus were also found to be 20% air saturation, respectively (Kojima, l995;Martin and McDaniel, 1975). The dierence between C crit for growth and production shows that additional dissolved oxygen requirements were needed for pneumocandin production.…”
Section: Separation Of the Impact Of Agitation And Dissolved Oxygensupporting
confidence: 64%
“…The interrelationship between fermentation parameters (such as agitation and dissolved oxygen) has made it historically dicult to separate eects on productivity for industrial fermentation processes. The sensitivity of secondary metabolite production to dissolved oxygen has been shown by a number of studies: cephamycin C (Yegneswaran et al, 1991), tylosin (Chen and Wilde, 1991), capreomycin (Feren et al, 1969), candicidin (Martin et al, 1975), dicidin (Suphantharika et al, 1994), erythromycin (Pollard et al, 1998), moranoline, (Kojima et al, 1995), and cephalosporin C (Hilgendorf et al, 1987;Rollins et al, 1991). Most examples are at laboratory scale and few have truly separated the impact of dissolved oxygen from agitation.…”
Section: Introductionmentioning
confidence: 96%
“…This model was originally developed for the formation of lactic acid by Lactobacillus delbrueckii [18]. According to this model, the product formation rate depends upon both the instantaneous biomass concentration, x, and growth rate, dx/dt, in a linear manner.…”
Section: Product Formationmentioning
confidence: 99%
“…The production of antibiotics started at 20 h, where the cells entered the midexponential phase and reached the max production at 136 h. The mutant strain consumed substrate efficiently, grew faster, and produced more antibiotic compared to the wild strain function. In many fermentation systems such as antibiotic fermentations by many types of microorganisms, cell growth has been characterized by the logistic equation [16][17][18]. The logistic equation can be described as :…”
Section: Microbial Growthmentioning
confidence: 99%
“…Various workers have demonstrated that penicillin synthesis is suppressed at DOT values below about 10% air saturation [3,4] and only reaches a maximum rate at higher DOT values. Critical DOT values below which synthesis is reduced have been reported for other antibiotics such as cephalosporins [5], cephamycin C [6] and candicidin [7]. We have previously reported [8] the effect of DOT on antibiotic production in a non-filamentous bacterium, Bacillus subtilis, which synthesises difficidin and its hydroxylated derivative, oxydifficidin [9] and a brief description of the work was reported earlier [10].…”
Section: Introductionmentioning
confidence: 95%